أول تسجيل لديدان النوع: (Euzet and Suriano, 1977) Ligophora mediterraneus على غلاصم أسماك البوري أفطس (Mugil cephalus) والبوري دهبان (Liza aurata) في مياه شاطئ اللاذقية - سورية - ديوب آمل; ديوب نسرين (Latakia University Journal -Biological Sciences Series, 2018)
أجريت الدراسة بهدف التقصي عن وجود الإصابة بالديدان وحيدات الجيل Monogenea على غلاصم النوعين السمكيين البوري أفطس (Mugil cephalus) والبوري دهبان (Liza aurata) في مياه شاطئ اللاذقية، وتحديد أنواعها، ومعدل انتشار الإصابة بها. جمعت العينات السمكية عشوائياً من موقعين مختلفين بظروفهما البيئية (منطقة مرفأ اللاذقية، منطقة مصب نهر الكبير الشمالي)، على شاطئ اللاذقية، باستخدام شباك الصيد، خلال الفترة الممتدة من تاريخ 8/6/2016 ولغاية 10/5/2017، بمعدل جولة/ الشهر. بينت نتائج الفحص المجهري للمسحات الرطبة المأخوذة عن غلاصم الأسماك المدروسة، وجود الإصابة بديدان النوع Ligophora mediterraneus، على غلاصم كلا النوعيين السمكيين المدروسين البوري أفطس والبوري دهبان بمعدل خمج عام 18.18%. أظهرت نتائج الدراسة أن أسماك البوري دهبان كانت أكثر عرضة للإصابة بديدان النوع L. mediterraneus من البوري أفطس بمعدل خمج 25%، 17.36% على التوالي، إلا أن أسماك كلا النوعين البوري أفطس والبوري دهبان المصطادة من منطقة مرفأ اللاذقية كانت أكثر إصابة بالطفيلي المذكور بمعدل خمج عام بلغ . 18.18% وكان أعلى ظهور لديدان النوع L. mediterraneus على غلاصم أسماك البوري المدروسة في كلا الموقعين في فصل الربيع بمعدل خمج عام 30.76% ، يليه فصل الصيف23.3%، بينما سجل أقل معدل إصابة في فصل الخريف. سجل النوع L. mediterraneus على غلاصم أسماك البوري أفطس والبوري دهبان في شاطئ مدينة اللاذقية لأول مرة في سورية في دراستنا هذه. The aim of the study was to detect the occurrence of monogenea worms on the gills of two fish species Mugil cephalus and Liza aurata in Lattakia coast, and to determine their species and prevalence rate. The fish samples were collected randomly from two sites, differing in their environmental conditions (Lattakia port site and Al-Kabeer Al-shamali river estuary site), on Lattakia coast, using fishing nets, during the period from 8/6/2016 to 10/5/2017; one time /month. The results of the microscopic examination of wet smears were taken from gills revealed infection by Ligophora spp. worms. The species Ligophora mediterranus was isolated and classified from gills of both studied fish species Mugil cephalus and Liza aurata in general prevalence rate 18.08%. The results showed that Liza aurata was more susceptible to L. mediterraneus than Mugil cephalus with infection rate of 25% and 17.36% respectively. However, both species ( Mugil cephalus and Liza aurata )that cought from Lattakia port were more infected with L. mediterraneus in a general infection rate of 18.18%. The highest occurrence of L. mediterraneus on gills of both fish speices in both studied sites was in Spring (30.76%), followed by Summer (23.3%), while the lowest incidence rate was in Autumn. The species L. mediterraneus on gills of Mugil cephalus and Liza aurata fish in Lattakia coast was recorded for the first time in Syria in this study.